Pengaruh Media Video Triase Hospital Emergency Severity Index terhadap Pengetahuan Mahasiswa Keperawatan Anestesiologi Universitas 'Aisyiyah Yogyakarta - Yoan Shalimar Pranatio; Muhaji Muhaji; Vita Purnamasari (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Triage is a crucial process in the management of emergency patients to determine the priority of treatment based on the severity of the patient's condition. One of the triage systems used is the Emergency Severity Index (ESI). This study aims to determine the effect of triage Hospital Emergency Severity Index (ESI) video media on the knowledge of anesthesiology nursing students at Universitas 'Aisyiyah Yogyakarta. This research employed a quasi-experimental design with a non-equivalent pretest-posttest control group approach. The sample consisted of 40 students divided into two groups: 20 in the intervention group and 20 in the control group. The research instruments included an educational video and a knowledge questionnaire. Data analysis was conducted using the Wilcoxon Signed Rank Test and Mann-Whitney test. The results showed a significant increase in knowledge in the intervention group after the video media was provided. The average knowledge score increased from 36.60 (pretest) to 70.05 (posttest), with the Wilcoxon test yielding a p-value of 0.001 (p < 0.05). In contrast, the control group showed no significant change with a p-value of 1.000, indicating a significant difference between the two groups. The triage Hospital Emergency Severity Index video media is effective in enhancing the knowledge of anesthesiology nursing students.